Acute and chronic effects of temperature on membrane adjustments in the gills of a neotropical catfish - Ribeiro, Cristiele da Silva [UNESP]; Schreiner, Matthias; Navas Iannini, Carlos Arturo; Gomes, Aline Dal'Olio; Tolussi, Carlos Eduardo; Moreira, Renata Guimaraes (Elsevier B.V., 2021)
Structural modifications in the gill membranes maintain homeostasis under the influence of temperature changes. We hypothesized that thermal acclimation would result in significant modification of phospholipid fatty acids, with modulation of sodium pump activity during acute (24 and 48 h) and chronic (15 days) thermal shifts in the neotropical reophilic catfish Steindachneridion parahybae. Indeed, the time-course experiment showed acute and chronic changes in gill membrane at the lowest temperatures, notably linked to maintenance of membrane fluidity: significant preferential changes in phosphatidylethanolamine, with decrease of saturated fatty acids and increase of C18:1 in all groups kept below 30 degrees C in chronic trial, increase in polyunsaturated fatty acids n6 and C18:1 at 17 and 12 degrees C compared to 24 degrees C, as soon as the temperature was changed (initial time). Additionally, the activity of the sodium pump increased at 12 degrees C, but without apparent connection with the altered lipid environment. The animals maintained at the lowest temperature showed a higher mortality, possibly because of the approach to the minimum critical temperature for this species, and unexpected results of changes in the fatty acid profile, such as decreased docosahexaenoic acid in phosphatidylethanolamine and increased saturated fatty acids in phosphatidylcholine. This set of mechanisms highlights rheostatic adjustments in this species in the face of temperature changes.
Keywords: Acclimation; Steindachneridion parahybae; Phospholipids; Fatty acids; Sodium pump